Dorsal-ventral patterning of the Drosophila embryo - Levine, Mike (Henry Stewart Talks, 2008)
The dorsal-ventral patterning of the early Drosophila embryo is controlled by a sequence-specific transcription factor called Dorsal, which is related to mammalian NF-κB, The Dorsal protein is distributed in a broad nuclear gradient, which generates different thresholds of gene activity, The mechanisms underlying these thresholds are likely to be relevant to a host of developmental processes in metazoan embryos
Reviewed at 2018/05/31